(3cJGH Gdadc hGdHQhLs - (3Sgd Hf HTQ Hf MHjH Hf gGfj, CHh YKeGf GdESQGFjdj,J (B235 (3g` s
(3ChdgG (B:s
(3GYde Cf GdHQhL GdCKfi YTQ efgG SJI PchQ hSJI CfGK s
(3BNQgG (B:s
(3HgG hba cGJH HYO bhdg JMeO ai WdH GdMhGFL ef GdcJGH hGdJLGQ hTQGA GdZdeGf hGdeeGdjc s
(3HgG fXGe JYbjHIs
(3HgG hbajI cGJHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B283s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3Gdadcs